Reducing Smoking Culture in Indonesian Communication Practices: An Intercultural Communication Perspective - Rita Gani; Lisa Adhrianti (Sekolah Tinggi Ilmu Kesehatan Sapta Bakti, 2026)
Background: Smoking culture in Indonesia is a sociocultural phenomenon shaped by communication practices, social norms, masculinity, and communal values. Although previous studies have mainly focused on biomedical and policy aspects, limited attention has been given to how communication contributes to the normalization of smoking behavior. This study aimed to analyze the role of communication in sustaining smoking culture and to identify communication-based strategies for cultural change. Method: This study used a qualitative descriptive design with a systematic literature review approach. Articles published between 2019 and 2025 were collected from Google Scholar, Scopus, and SINTA databases using relevant keywords related to smoking culture and health communication. Data were analyzed thematically to identify dominant communication patterns associated with smoking behavior. Result: The findings show that smoking normalization is reinforced through cigarette-sharing practices, peer interactions, positive language framing, and representations of masculinity. These communication patterns position smoking as a symbol of social acceptance and cultural identity. Several communication-based interventions were also identified, including digital health literacy, family-centered campaigns, smoke-free public space promotion, and the reconstruction of smoking-related social symbols. Conclusion: Smoking culture persists because communication continuously reproduces social acceptance and collective identity surrounding smoking behavior. The findings highlight the importance of symbolic interaction in shaping health behavior and suggest that culturally sensitive communication strategies are needed to reduce smoking normalization and strengthen tobacco control efforts in Indonesia.